Arduino: uma alternativa para aulas experimentais de física, auxiliada pelo ensino hibrido - Andrade Filho, Josias Amaral de (2020)
Teaching physics in high school using a blackboard and a brush, the traditional way, has demotivated some students, in order to create alternatives such that students have greater interests in the discipline, we propose in this work the use of hybrid education, which combines o ine teaching and online teaching, in its laboratory rotation model. In this model, students go through all educational stations, carrying out the proposed activities. We made use of the educational spaces available at the school, which are: the science lab, the computer lab, and a virtual learning environment, Google Classroom as a tool for the student's technological inclusion. Circuit simulation software, tinkecard, fritzing for its construction and Arduino were also used. With the application of these tools, students are given the possibility to build virtual and physically proposed circuits. Two experiments were carried out, one to determine the speci c heat of aluminum, using the temperature sensors LM35 and Ds18b20, and the other to measure the voltages and resistances in real time of an LDR sensor together with an animation created by the students themselves in Hackeduca platform. To obtain the results, Newton's cooling laws and Ohm's law were applied to obtain their values, and their results were then compared with those of existing literature and some re ections were made. As a nal product, we developed a Didactic Sequence, containing all the stages of the work application. This work was applied in a high school in the area of the city of Manaus, with the participation of twenty students from the third year of high school. Upon completing this work, we veri ed a greater interaction of students and their interest.